AGROBIOLOGICAL ASSESSMENT OF SEA BUCKTHORN VARIETIES IN THE CONDITIONS OF TRANSCARPATHIAN REGION - Savina О.; Popovych Г.; Sheidyk К. (Bulletin of Lviv National Environmental University. Series Agronomy, 2024)
The research is focused on adapting and spreading introduced varieties of sea buckthorn in Transcarpathian region. Sea buckthorn has recently become a highly sought-after crop for organic product production. The research utilized the introduced varieties Askoli and Adam to create popular nursery material. Green cuttings were primarily used for propagation, allowing for the production of genetically uniform plants. The research was carried out at the Continent agro-firm in the Perechyn district of Transcarpathian region from 2022 to 2023. The study included examining the growth and pruning characteristics of mother stock trees to promote shoot growth and reduce labor costs during harvest. It was determined that annual plant growth depends on weather conditions, tree age, and pruning intensity. The adaptability of introduced varieties to changing growing conditions and the development of technology for growing mother stock trees for propagation using hardwood cuttings were also closely examined. The results of the research indicated that sea buckthorn forms with significant annual shoot length show promise as they lead to increased yields in the following year. The analysis suggested that variations in plant growth could be attributed to weather conditions and technological support. It was observed that the greatest growth occurred in favorable weather years, while growth was significantly less in dry years. Additionally, the research paid significant attention to the morphological features of the plants, including crown shape, branching and thorniness degree, shoot and peduncle length, and fruit characteristics. Plant decorativeness was evaluated using a comprehensive scale of decorative features. The research demonstrated that it is feasible to successfully grow introduced sea buckthorn varieties in Transcarpathian region, obtain yields by cutting branches, and utilize effective pruning methods to increase productivity. Practical recommendations for growing and propagating sea buckthorn in the region were developed based on the data obtained.